(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
A study of pepper leaves (Piper nigrum L.) ethanol extract anti-hyperuricemia activity in mice has been done. The aim of this study was to know the effect of administration, to look for the best dose and to know the potency of pepper leaves ethanol extract in decreasing uric acid level of mice (Mus musculus L,). The method was in vivo anti-hyperuricemia activity using potassium oxonate-induced hyperuricemia mice. The mice were divided into 5 groups, i.e negative control, positive control, extract dose of 12.5 mg/kg BW, extract dose of 25 mg/kg BW and extract dose of 50 mg/kg BW. Each group consisted of 3 mice. The test substances were given orally at 0.75 hours after the induction of potassium oxonate then uric acid levels were measured at 1; 1.5; 2; 2.5 and 3 hours after induction. Uric acid levels of mice were measured using a test-strip uric acid. The results were analyzed visually by an average of the measured data and graphs. The results showed that the pepper leaves ethanol extract dose of 12.5 mg/kg BW, 25 mg/kg BW and 50 mg/kg BW capable to inhibit the increase of uric acid levels. The best dose was 25 mg/kg BW, but based on observation, it was not better than the positive control allopurinol.